2009
DOI: 10.1525/as.2009.49.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Afghanistan in 2008: State Building at the Precipice

Abstract: The state-building endeavor in Afghanistan came to the brink in 2008 with the Taliban insurgency taking control of some southern districts, high poppy production fueling the illicit economy, widespread charges of corruption, and a looming humanitarian disaster. Afghans increasingly became disillusioned by high civilian casualties and the government's failure to provide improved socioeconomic conditions. By year's end, there was also increased pressure for negotiations with moderate Taliban elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, at least until the strategic review undertaken by COMISAF Stanley McChrystal in the summer of 2009, counter-insurgency efforts were characterised by the destruction of property, a heavy reliance on air power and high numbers of civilian casualties -aspects of kinetic operations at odds with the cultivation of local support. 76 McChrystal's shift of emphasis to greater respect for property and the minimising of civilian casualties was not a priority for his successors Generals David Petreus and John Allen. Air strikes, night raids and consequent civilian casualties have remained a feature of ISAF operations thereby contributing to widespread local scepticism over the benefits of the NATO mission.…”
Section: Localmentioning
confidence: 99%
“…However, at least until the strategic review undertaken by COMISAF Stanley McChrystal in the summer of 2009, counter-insurgency efforts were characterised by the destruction of property, a heavy reliance on air power and high numbers of civilian casualties -aspects of kinetic operations at odds with the cultivation of local support. 76 McChrystal's shift of emphasis to greater respect for property and the minimising of civilian casualties was not a priority for his successors Generals David Petreus and John Allen. Air strikes, night raids and consequent civilian casualties have remained a feature of ISAF operations thereby contributing to widespread local scepticism over the benefits of the NATO mission.…”
Section: Localmentioning
confidence: 99%
“…As much as one-third of the country is controlled by these factions (Dale, 2009). One specific event that exemplified this gradual Taliban resurgence was the June 12, 2008 Taliban attack against the Sarposa prison in Qandahar that resulted in freeing 1200 inmates (Katzman, 2008;Mullen, 2009). In addition, both U.S. and international assessments have continuously indicated that the Afghan government is largely failing to stabilize the country, and areas that were previously considered secure, such as in the capital of Kabul, have experienced an increase in the number of military and civilian deaths (Katzman, 2008).…”
Section: The Problemmentioning
confidence: 99%